The enhancement of nutrition value of maize by biotechnology - Thanh, Nguyen Duc (Academia Journal of Biology, 2016)
The demand on maize is increasing both in the world and Vietnam. While, as other cereals, maize is low in important nutrition compounds, especially, lysine, vitamin A, folic acid, iron, zinc and selenium. Therefore, there have been many attempts in the researches on improvement of nutrition value of cereal crops, in general, and maize, in particular. This article reviews the published results obtained from the studies aimed to enhance maize nutrition value by biotechnological tools. Especially, the progress in the improvement of protein quality, carotenoid content and micro-nutrition elements such as ferrous and zinc will be highlighted. The published results showed bright prospect for the improvement of nutrition value of maize and other cereal crops as well as the issues that need the further investigation. Citation: Nguyen Duc Thanh, 2017. The enhancement of nutrition value of maize by biotechnology. Tap chi Sinh hoc, 39(1): 1-14. DOI: 10.15625/0866-7160/v39n1.7909. *Corresponding author: nguyenducthanh_pcg@ibt.ac.vn. Received 17 March 2016, accepted 20 March 2017